Scoping review : teaching personal and social responsibility through physical activity (TPSR-MODEL) - Pienimäki, Iita (2019)
Teaching personal and social responsibility model (TPSR)is a physical activity program, which was originally created for underserved youth and has been used in physical activity programs and as a curriculum model in physical education in several countries around the world. TPSR has been widely used for decades but its empirical support has been criticized in the academic world. The purpose of this study was to conduct a scoping review to examine the published literature on TPSR. This scoping review followed the methodological framework provided by Arksey and O’Malley (2005) and used electronic databases (PsycINFO, Sportdiscus, ERIC, Science and Technology, Physical Education Index, and CINAHL) and TPSR alliance’s reference list to locate relevant publications. Articles, which were included in this review were empirical research studies, written in English, and the intervention and/or instructor’s training had to be thoroughly described. Of the 169 articles initially identified, 43 studies met the inclusion criteria. The trend of TPSR research has remained the same since the model begun to interest the scientific world. Majority of the chosen studies were conducted in the United States (60%) while the qualitative methodology was the most common choice for research methodology (65%). Out of 43 chosen studies, 30 were identified as interventions of the model. Interventions varied in terms of duration and instructor’s background and training. The most popular duration for the interventions was 7-12 months (37%) and teaching background for the instructor accounted for 47% of the chosen interventions. Training of the instructor for the TPSR model wasn’t mentioned in one third of the chosen studies (30%). Four of the interventions were controlled trials and two of those were randomized controlled trials (5%). Using TPSR as a curriculum model in order to teach responsibility by using sports as a vehicle for learning is valid according to the published studies. To extend the TPSR research to a more systematic direction in the future, adding guidelines to intervention implementation and reporting is recommended.